Analysis of the Implementation of Malay Oral Tradition in Indonesian Language Learning for Student Character Formation at Kasih Karunia Junior High School - Anggi Nur Febriani; Tia Maharani; Siti Azura; Nurul Asiyah Syahkila; Fitriani Lubis (Journal of English Language and Education, 2026)
Indonesian language instruction plays a crucial role in developing both students' language skills and character. However, instruction in schools still tends to focus on cognitive aspects and has not yet optimally integrated local culture as a learning resource. This study aims to analyze the implementation of Malay oral traditions in Indonesian language instruction and their role in shaping student character at SMPTK Kasih Karunia. The study employed a qualitative descriptive approach, involving one Indonesian language teacher and five students as research informants. Data were collected through in-depth interviews and analyzed using qualitative descriptive analysis techniques, following the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Malay oral traditions, particularly Syair Perahu by Hamzah Fansuri, have been incorporated into the teaching of classical poetry through activities focused on structural analysis, symbolic meaning, and moral values. The integration of oral traditions makes learning more contextual, enhances student engagement, and helps instill religious values, responsibility, good manners, and social awareness. Students showed positive responses because the learning material was related to their culture and daily experiences. This study indicates that the Malay oral tradition has the potential to serve as a medium for Indonesian language instruction that supports character education while also contributing to the preservation of local culture within the school environment.